The role of the renin–angiotensin system in regulating endometrial neovascularization during the peri-implantation period: literature review and preliminary data - Ruofan Qi; Tin Chiu Li; Xiaoyan Chen (Therapeutic Advances in Endocrinology and Metabolism, 2020)
Background: Implantation is initiated when the blastocyst attaches to the endometrium during the peri-implantation period, and appropriate neovascularization is a prerequisite for the success of the subsequent process. The role of the renin–angiotensin system (RAS) in regulation of blood pressure and hydro-electrolyte balance has long been recognized, while its role in the peri-implantation endometrium remains unclear. This manuscript discusses endometrial RAS and its possible pathways in regulating endometrial angiogenesis and its influence on subsequent pregnancy outcomes. Methods: A comprehensive search of electronic databases was carried out to identify relevant published articles, and a literature review was then performed. Using immunohistochemistry, we also performed a pilot study to examine expression of angiotensin II receptors, including angiotensin II type 1 (AT1) receptor (AT1-R) and angiotensin II type 2 (AT2) receptor (AT2-R) in the human endometrium around the time of implantation. Results: The results of the pilot study showed expression of AT1-R and AT2-R in all endometrial compartments (luminal epithelium, glandular epithelium, stroma cells, and blood vessels), and altered expression was witnessed in women with recurrent miscarriage when compared with fertile control women from our preliminary result. Conclusion: Altered vasculature of the endometrium in the peri-implantation period is detrimental to implantation and may lead to recurrent miscarriage. Being an angiogenic mediators, endometrial RAS may play a role around the time of embryo implantation, affecting subsequent pregnancy outcomes.